2005
DOI: 10.4049/jimmunol.175.5.3299
|View full text |Cite
|
Sign up to set email alerts
|

Complement Regulator-Acquiring Surface Protein 1 Imparts Resistance to Human Serum in Borrelia burgdorferi

Abstract: Factor H and factor H-like protein 1 (FH/FHL-1) are soluble serum proteins that negatively regulate the alternative pathway of complement. It is now well recognized that many pathogenic bacteria, including Borrelia burgdorferi, bind FH/FHL-1 on their cell surface to evade complement-mediated destruction during infection. Recently, it was suggested that B. burgdorferi open reading frame bbA68, known as complement regulator-acquiring surface protein 1 (CRASP-1), encodes the major FH/FHL-1-binding protein of B. b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
156
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 114 publications
(159 citation statements)
references
References 57 publications
3
156
0
Order By: Relevance
“…In fact, B. burgdorferi was shown previously to successfully display surface-exposed lipoproteins, e.g., Vsp1 and Vsp2 of relapsing fever borreliae (55). In addition, the complementation of BbCRASP-1 or BbCRASP-2 expression in serum-sensitive borrelial cells imparts resistance to human serum (27,29). Here we demonstrate that expression of the BhCRASP-1 of relapsing fever borreliae in the serum-sensitive Lyme disease spirochete B. burgdorferi B313 results in an increased resistance of the mutant strain to complement-mediated killing, suggesting the involvement of BhCRASP-1 in the immune evasion of B. hermsii.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, B. burgdorferi was shown previously to successfully display surface-exposed lipoproteins, e.g., Vsp1 and Vsp2 of relapsing fever borreliae (55). In addition, the complementation of BbCRASP-1 or BbCRASP-2 expression in serum-sensitive borrelial cells imparts resistance to human serum (27,29). Here we demonstrate that expression of the BhCRASP-1 of relapsing fever borreliae in the serum-sensitive Lyme disease spirochete B. burgdorferi B313 results in an increased resistance of the mutant strain to complement-mediated killing, suggesting the involvement of BhCRASP-1 in the immune evasion of B. hermsii.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, for the closely related spirochete Borrelia burgdorferi, the causal agent of Lyme disease, a strong correlation between the serum resistance of a given isolate and its expression profile of FH-binding outer surface lipoproteins, termed complement regulator-acquiring surface proteins (CRASP), was reported (20 -28). Moreover, it was suggested that the dominant FH binding molecule of serum-resistant B. burgdorferi strains, BbCRASP-1, is necessary to resist killing by human serum (29). Some bacteria, such as Porphyromonas gingivalis, Pseudomonas aeruginosa, and Clostridium perfringens, produce their own proteolytic enzymes that digest the extracellular matrix to facilitate invasion (30).…”
mentioning
confidence: 99%
“…B. burgdorferi produces up to five different BbCRASPs, which are reviewed herein. At least two of the BbCRASPs contribute to complement resistance in vitro (Brooks et al, 2005;Hartmann et al, 2006) but the question of why B. burgdorferi produces multiple distinct factor H-binding proteins remains unsolved. Confounding matters further, both wild-type and factor H-deficient mice can be infected by Lyme disease spirochetes to equal degrees , suggesting that factor H-binding is not essential for efficient mammalian infection.…”
Section: Introductionmentioning
confidence: 99%
“…Differential gene expression plays a critical role in the transmission, colonization, and dissemination of B. burgdorferi in mammalian hosts. Several of these open reading frames (ORFs) include mediators that provide a selective advantage to B. burgdorferi by enhancing its ability to adhere to host matrices (24,39,64) and to evade the mediators of innate and adaptive immunity (16,26,48,89), as well as other deleterious physiological processes encountered in its hosts (27). A number of studies have determined the significance of alterations of surface lipoproteins in response to these signals, and the molecular mechanisms responsible for these changes are beginning to be understood (41,86).…”
mentioning
confidence: 99%